Silage from heart-of-palm waste produced from Alexander palm tree - Bayão, Geraldo F. V.; Queiroz, Augusto C.; Pimentel, Róberson M.; Freitas, Samuel G.; Sousa, Katiene R. S.; Cardoso, Lucas L.; Marcondes, Marcos I.; Batalha, Camila D. A.; Oliveira, Gabriel B.; Silva, Tadeu E. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Production of heart-of-palm from Alexander palm tree generates a waste that could be used as silage for feeding ruminants. Objective: To evaluate the chemical composition, fermentation parameters, and quality of silage made from waste of heart-of-palm production using Alexander palm. Methods: Three types of silage made from waste of heart-of-palm production were evaluated: 1) leaf silage, 2) sheath silage, and 3) compound (leaf + sheath) silage. The processed waste was packed in experimental silos and distributed in a completely randomized design with 10 replications. Means were compared pairwise using Tukey’s test at the 5% significance level. Results: Leaf silage had the highest pH (p<0.05) and the lowest ammonia nitrogen (p<0.05) in relation to the other silages. No difference was observed (p>0.05) for lactic and butyric acids, whereas acetic acid was higher (p<0.05) in the sheath and compound silages. Dry matter and crude protein contents were the highest (p<0.05) in leaf silage. Neutral detergent fiber was higher (p<0.05) in sheath silage, followed by leaf and compound silages, respectively. The highest lignin content (p<0.05) was observed in sheath silage. Conclusions: Based on the fermentative parameters, waste from heart-of-palm from Alexander palm tree has potential for silage production. However, differences in silage composition at the time of feeding ruminants should be considered.